The Christian faith and evolution: An evolving, unresolved debate - Conradie, Ernst M. (Verbum et ecclesia, 2018)
This article sketches how the debate on Christian faith and evolution has evolved. Seven challenges are identified and described in the debate, namely, regarding a recognition of deep (geological) time (challenging the historicity of the biblical creation narratives), understanding the role of chance in natural selection (posing questions about the nature of divine action, e.g., providence), human descent (challenging presumed human distinctiveness), a recognition of natural suffering (challenging the benevolence of the Creator), identifying the evolutionary roots of evil (challenging Christian views on the fall of humanity), a recognition of natural disselection (challenging notions of divine election) and, finally, evolutionary explanations of the emergence of morality and of religion (reiterating the challenge of atheism). It is argued that with each of these challenges, some of the underlying problems were provisionally resolved, only to reappear later in an even more challenging form.Intradisciplinary and/or interdisciplinary implications: The contribution describes shifts in Christian discourse on evolution and challenges the tacit assumption that any one aspect of the debate has been fully resolved by articulating some of the questions that have been resolved and others that remain unresolved.